Noise and competition in strategic oligopoly - Dridi, Ramdan; Germain, Laurent (Journal of Financial Intermediation, 2009)
In this paper, we propose a model where N strategic informed traders who are endowed with heterogeneous noisy signals with different precisions compete in a market with a single risky asset. We explicitly describe the unique linear equilibrium that exists in this setup and derive its properties. Moreover, we focus on the effects of noise on the competition between traders. We show that noise softens the competition between traders. In particular, for N exceeding three and for certain sets of noise in traders' signals, each trader's individual profit is greater than the one obtained in the case of perfect information.